Contents of Serum P-selectin As An Early Marker of Endothelium Dysfunction and Atherosclerotic Changes in Patients with Chronic Kidney Disease - Khurshidakhon Abduboriyevna, Rasulova; Botir Turgunpulatovich, Daminov; Aziz Kabilovich, Abbasov (International Journal of Psychosocial Rehabilitation, 2020)
Objective: to study the content of P-selectin in the blood of patients with chronic kidney disease (CKD) and evaluate its effect on the development of endothelial dysfunction (ED) and atherosclerotic changes. Material and methods: In 65 patients with CKD (average age 61.2 ± 1.7 years), the level of P-selectin in the blood serum was determined. The control group consisted of 20 relatively healthy individuals without CKD, comparable in age and sex with the study group. All patients analyzed the data of clinical, laboratory, and instrumental methods of research. The diagnosis of CKD was made in accordance with the recommendations of KDIGO (2012) and ICD-10. The content of P-selectin in the selected and frozen blood sera of patients was determined by the method of enzyme-linked immunosorbent assay. Results. With CKD, a violation of immune homeostasis associated with clinical manifestations was revealed, characterized by significantly higher serum P-selectin values. However, when it is increased, the concentration of P-selectin in the blood depends on the stage and category of CKD: as GFR decreases (59 ml/min/1.73 m² or less), the serum level of P-selectin significantly decreases, especially with CKD stage III-V. In patients with CKD with clinical, laboratory, and instrumental signs of ED and atherosclerosis, the level of P-selectin increases more significantly compared with patients with CKD without atherosclerotic changes. There is a close relationship between the level of P-selectin and various clinical and biochemical syndromes of kidney pathology. As the inflammatory process, hypercholesterolemia, urinary and nephrotic syndromes, as well as arterial hypertension syndrome, the concentration of P-selectin increases. However, with uremia and hypercreatininemia, serum P-selectin levels decrease. Conclusions. The established abnormalities are based on the inflammatory process in the kidneys and activation/dysfunction of the endothelium and platelets. The deepening imbalance of the mediator of intercellular interactions of P-selectin with the progression of CKD (up to the terminal stage) and the presence of a relationship with various clinical options for renal pathology are evidence of the important clinical and pathogenetic significance of selectin disorders in the progression of the process and the formation of atherosclerotic changes and other complications of CKD.